Sensitivity and specificity of mean corpuscular hemoglobin (MCH): For screening alpha-thalassemia-1 trait and beta-thalassemia trait - Savitree Pranpanus (2018)
Objective: To evaluate sensitivity, specificity, and positive and negative predictive value of mean corpuscular hemoglobin (MCH) for screening alpha-thalassemia-1 trait and beta-thalassemia trait Material and Method: Descriptive analysis, diagnostic test, was conducted on 396 pregnant women attending the antenatal clinic between September 2007 and June 2008. Blood samples were collected from pregnant women after counseling and getting informed consent. MCH was measured in all samples by automated hematology analyzer. Determination of HbA2 level for diagnosis of beta-thalassmia trait and PCR for alphat-halassemia-1 gene (SEA type) were performed in all cases as a gold standard. The data were collected and analyzed for sensitivity, specificity, and positive and negative predictive value of MCH for screening alpha-thalassemia-1 trait and beta-thalassemia trait. Results: Based on the ROC curve, the best cut-off level of MCH in predicting the thalassemia carriers was 26.5 picrograms. Positive MCH (< 26.5 picrograms) gave the sensitivity of 95.2% and specificity of 82.3% in screening alpha-thalassemia-1 trait and beta-thalassemia trait. The positive predictive value and negative predictive value were 40.4% and 99.3% respectively. Conclusion: MCH is a good tool for screening alpha-thalassemia-1 trait and beta-thalassemia trait during pregnancy because of its simplicity, low cost, (when determined as a part of complete blood count), and high sensitivity.